Pemodelan Struktural Dermaga dengan Variasi Tiang Pancang Menggunakan SAP2000 - N. Rizkillah, Sasti; Imananto, E.I.; Yudianto, E.A. (Tadulako University, 2026)
Wharf structures operate in complex marine environments and are subjected to significant lateral loads from berthing forces, sea currents, and wave actions that affect structural behavior and foundation performance. One common method to improve lateral resistance is the use of inclined piles, which convert part of the horizontal load into axial compressive force. This study develops a numerical structural model of a wharf with variations in pile inclination from vertical to inclined configurations, limited to the modeling stage. Finite element modeling is carried out using SAP2000 based on wharf geometry, material properties of concrete and steel, soil parameters from site investigation data, and service load combinations representing operational conditions. All pile inclination models are analyzed using identical parameters to ensure consistent comparison. The evaluated responses include axial force, shear force, bending moment, and global lateral displacement of the wharf. The results show that the vertical pile configuration produces the largest lateral displacement of 0.147 m and high bending moments, indicating a flexible lateral response. As pile inclination increases, axial force rises from 6,471.024 kN and reaches a maximum of 6,496.89 kN at an intermediate inclination, while bending moments gradually decrease. Lateral displacement is reduced and reaches a minimum value of 0.133 m at the same inclination. Further increases in pile inclination lead to higher shear force and a gradual increase in lateral displacement despite lower bending moments. These results confirm that inclined piles improve the lateral performance of wharf foundations, with intermediate inclination providing the most balanced response between axial force, bending moment, and lateral displacement